2011
DOI: 10.2500/ajra.2011.25.3663
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Medialization of Medial Rectus Muscle as a New Endoscopic Technique for Approaching Intraconal Lesions

Abstract: Although technically challenging, the endoscopic approach to the orbit, even for intraconal lesions with medialization of the medial rectus muscle, can be safe and promising for well-selected cases. Good postoperative results and sufficient material acquisition for proper histological examination can be obtained. Advantages are good visualization of the surgical field and avoidance of external scars. Limitations to endoscopic techniques are tumors in the lateral superior and lateral inferior quadrant of the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 13 publications
0
43
0
3
Order By: Relevance
“…Twelve papers were identified and included which contained patient data for 17 cases [5][6][7][8][9][10][11][12][13][14][15][16]. Six patients were male and eleven were female.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve papers were identified and included which contained patient data for 17 cases [5][6][7][8][9][10][11][12][13][14][15][16]. Six patients were male and eleven were female.…”
Section: Resultsmentioning
confidence: 99%
“…In 1999, Herman et al reported a case of endoscopic transnasal excision of an intraorbital hemangioma . Several other related studies have also been reported . Endoscopic techniques mainly are used in surgery on medial orbital optic nerve tumors, but the literature is still quite heterogeneous due to the complexity of the intraorbital anatomy and widely varying relationship of the tumor to critical neurovascular structures.…”
mentioning
confidence: 99%
“…13,14 Tomazic et al 13 Copyright (c) Oceanside Publications, Inc. All rights reserved. For permission to copy go to https://www.oceansidepubl.com/permission.htm date when using the transchoanal method with 2-0 silk thread for MRM retraction around the choana.…”
Section: Discussionmentioning
confidence: 94%
“…The heights of exposure in the vertical dimension were 4.51 Ϯ 1.56 mm for the external group, 12.53 Ϯ 4.38 mm for the transseptal group, 13.05 Ϯ 5.86 mm for the choanal group, and 13.57 Ϯ 3.74 mm for the transseptal double ball group (Table 1). A graphic representation of these data by using box and whisker plots is seen in Fig.…”
Section: Height Of Exposurementioning
confidence: 99%